Systematic Review, Meta-analysis, and Cost-effectiveness of Treatment of Latent Tuberculosis to Reduce Progression to Multidrug-Resistant Tuberculosis - Marks, Suzanne M; Mase, Sundari R; Morris, Sapna Bamrah (Clinical infectious diseases, 2017)
Evidence-based recommendations for treating persons having presumed latent tuberculosis (LTBI) after contact to infectious multidrug-resistant (MDR) tuberculosis (TB) are lacking because published data consist of small observational studies. Tuberculosis incidence in persons treated for latent MDR -TB infection is unknown. We conducted a systematic review of studies published 1 January 1994-31 December 2014 to analyze TB incidence, treatment completion and discontinuation, and cost-effectiveness. We considered contacts with LTBI effectively treated if they were on ≥1 medication to which their MDR-TB strain was likely susceptible. We selected studies that compared treatment vs nontreatment outcomes and performed a meta-analysis to estimate the relative risk of TB incidence and its 95% confidence interval. We abstracted data from 21 articles that met inclusion criteria. Six articles presented outcomes for contacts who were treated compared with those not treated for MDR-LTBI; 10 presented outcomes only for treated contacts, and 5 presented outcomes only for untreated contacts. The estimated MDR-TB incidence reduction was 90% (9%-99%) using data from 5 comparison studies. We also found high treatment discontinuation rates due to adverse effects in persons taking pyrazinamide-containing regimens. Cost-effectiveness was greatest using a fluoroquinolone/ethambutol combination regimen. Few studies met inclusion criteria, therefore results should be cautiously interpreted. We found a reduced risk of TB incidence with treatment for MDR-LTBI, suggesting effectiveness in prevention of progression to MDR-TB, and confirmed cost-effectiveness. However, we found that pyrazinamide-containing MDR-LTBI regimens often resulted in treatment discontinuation due to adverse effects.